DEVELOPMENT OF PILOT PLANT FOR BIO-ETHANOL PROCESSING - Elisante, Emrod (Tanzania Journal of Engineering and Technology, 2017)
The paper outlines achievements obtained in developing a pilot bio-ethanol plant at the Department of Chemical and Mining Engineering (CME), University of Dar es Salaam. The pilot plant consists of: 30 L inoculums tank; 1,700 L fermenter; 1,500 L/day distillation column; and ancillary equipment. The prototype is a platform intended to be used for technology demonstration and research by graduate and undergraduate students studying the production of bio-ethanol using traditional and non-traditional raw materials like coffee mash, cashew fruit, and sisal inulin. The equipment has been developed using locally available engineering resources and the distillation column with 18 sieve tray measures 0.5 m diameter 7 m high operates at atmospheric pressure. The condenser is cooled by 15 o C chilled water from utility lines and the reboiler is powered by 63 kW boiler installed at CME. Although the system includes biological, chemical and mechanical engineering details, only the important design issues are presented. A MATLAB code was developed for estimating the number of theoretical plates using the Mc Cabe-Thiele method. The water- ethanol vapour liquid equilibrium VLE data was obtained using relative volatilities estimated by Antoine equations for vapour pressure. The process design was done using various simulation packages and custom programs like Microsoft Excel for mass balance, Microsoft Visio for process and instrumentation (P&I) diagram AutoCAD software for mechanical engineering drawings. After performing hydraulic leak tests, the prototype was tested using blackstrap molasses 80 o brix which was prepared for fermentation using dilution and inoculums formulations developed in Microsoft Excel for water dilution, yeast and nutrients like (NH 4 ) 2 SO 4, KH 2 PO 4, MgCl 2. A batch mash boiling test conducted on the column showed that the response of tray temperatures exhibited first-order delay behavior with an average lag of 17 minutes and a delay of 50 -65 minutes depending on tray distance from the reboiler. Due to lack of feedback control equipment specifically on-line composition analyzers and suitable actuators, continuous control of ethanol composition could not be undertaken. It is planned to procure pertinent control hardware during the next phase of the project. However the batch test gave initial ethanol purity of 80% which decreased as the ethanol content in the still was continuously depleted.